STATION ROTATION MODEL WITH ICT INTEGRATION ENHANCES STUDENTS’ PROBLEM SOLVING SKILL IN PHYSICS - Unsi, Alibai; Cauring, Alnoury; Camua, Amour; Dalgan, Norma (Advances in Social Sciences Research Journal, 2021)
Station rotation model has recently become a promising innovation in education in which learners lead to deeper learning and problem-solving development (Jones, 2018). The study determined the effectiveness of station rotation model with ICT integration to enhance the problem solving skill of ninth grade students of ARMM Regional Science High School during five weeks of intervention. The data of this study were obtained from the pre-test and post-test with open-ended questions from Control and Experimental Groups. These tests were administered before and after the intervention and scored using rubric. Moreover, attitude test was answered by the students to provide feedbacks on the use of station rotation model with ICT integration. Results revealed that there is no significant difference in the post-test performances under the Control Group (K-12 teaching instruction) and the Experimental Group (SRM with ICT Integration), t (25) =-1.324, p=.197. At the end of the study, experimental group under station rotation model with ICT integration does not significantly enhance students’ problem solving skill in Physics.